Contrasting short-term temperature effects on the profiling of metabolic and stress hormones in non-obese healthy adults: A randomized cross-over trial - Makris, Konstantinos C.; Konstantinou, Corina; Perikkou, Anastasia; Zdravic, Ana B.; Christophi, Costas A. (My University, 2020)
The manifestation of elevated and sustained air temperature gradient profiles in urban dwellings represents an emerging planetary health phenomenon. There is currently limited evidence about the effect of elevated air temperatures on metabolic health. The aim of this work was to assess changes in metabolic and stress hormonal profiles during a short-term stay in a mountainous, climate-cooler setting against those observed in the urban setting. A prospective, randomized, 2 x 2 cross-over trial of non-obese healthy adults in urban and mountainous areas of a Mediterranean country (Cyprus) was set up during summer, under real-life conditions. The intervention was a short-term stay (mean ± SD: 7 ± 3 days) in a mountainous, climate-cooler setting (altitude range: 650-1200 m), being ~1-h drive away from the main urban centres of Cyprus. The primary endpoint was the change in metabolic hormones levels (leptin and adiponectin) and stress hormone levels (cortisol) between the two settings. Personal air and skin temperature sensors were deployed while biospecimen were collected in each setting. A total of 41 participants between 20 and 60 years old were enrolled and randomized during July 2018, of whom 39 received the allocated intervention, 8 were lost to follow up or excluded from analysis and a total of 31 participants were analysed. A significant leptin reduction (β = -0.255; 95% CI: -0.472, -0.038; p = 0.024) was observed for non-obese healthy adults during their short-term stay in the mountainous environment. The intervention effect on adiponectin or cortisol levels was not statistically significant (β = 0.058; 95% CI: -0.237, 0.353; p = 0.702), and (β = -0.026; 95% CI: -0.530, 0.478; p = 0.920), respectively. In additional analyses, daily max skin temperature surrogate measures were significantly associated with leptin levels (β = 0.34; 95% CI: 0.051, 0.633; p = 0.024). During summer season, a short-term stay in climatologically cooler areas improved the leptin levels of non-obese healthy adults who permanently reside in urban areas of a Mediterranean country. A larger sample is needed to confirm the trial findings that could provide the rationale for such public health interventions in climate-impacted urban areas of our planet.
Keywords: Climate change; Exposome; Temperature; Non-pharmacological trial; Sensors; Metabolic; Hormone; Stress